Efektywność pracy oczyszczalni hydrofitowej o przepływie pionowym = Effectiveness of vertical flow constucted wetland - Bydałek, Franciszek; Myszograj, Sylwia (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The article describes the results of effectiveness of on-site vertical flow constructed wetland. Legal wastewater discharge limits were all fulfilled, reaching high, very consistent BOD and COD removal rates of 98% and 93,4% respectively. Effectives of nitrogen and phosphorus removal was low, yet in both cases obtained results were within characteristic range for such a systems. Concentration of total nitrogen was decreased by 12,7% and 13,4% for total phosphorus.
Keywords: przydomowe oczyszczalnie ścieków; systemy hydrofitowe; czynniki środowiskowe; on-site wastewater treatment; vertical flow constructed wetland; environmental factors